The Contributions of the Gulf of Maine Council to Regional Climate Resilience - Jordan, Pamela (Maine Policy Review, 2023)
This article investigates Canada-US collaboration in support of climate resilience efforts in the Gulf of Maine by focusing on the work of the binational Gulf of Maine Council on the Marine Environment (GOMC). Despite lacking authority over coastal management policymaking, the GOMC made significant progress between 2004 and 2022 towards achieving its climate resilience goals. Most importantly, GOMC actors, including members of the Climate Network, have helped build capacity for more effective measurement, monitoring, and analysis of climate change impacts in the Gulf of Maine. While its participants share common values and support rigorous climate action and marine conservation measures, the GOMC itself has been underdeveloped as a binational collaborative tool due to its limited mandate, financial resources, and small staff.